2019
DOI: 10.1097/qai.0000000000002042
|View full text |Cite
|
Sign up to set email alerts
|

Current US Guidelines for Prescribing HIV Pre-exposure Prophylaxis (PrEP) Disqualify Many Women Who Are at Risk and Motivated to Use PrEP

Abstract: Section 1 Diagnoses of HIV Infection and Diagnoses of Infection Classified as Stage 3 (AIDS) 1a Diagnoses of HIV infection, by year of diagnosis and selected characteristics, 2012-2017-United States 1b Diagnoses of HIV infection, by year of diagnosis and selected characteristics, 2012-2017-United States and 6 dependent areas 2a Stage 3 (AIDS), by year of diagnosis and selected characteristics, 2012-2017 and cumulative-United States 2b Stage 3 (AIDS), by year of diagnosis and selected characteristics, 2012-2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 26 publications
2
53
0
Order By: Relevance
“…Nevertheless, it is important to highlight that there was a substantial number, varying according to the guideline used, of HIV seroconversions among ineligible participants. It was previously shown that the US CDC criteria failed to identify a considerable proportion of individuals at risk for HIV [9,16,17], and the same was observed in this study and for the other guidelines. Previous research also suggests that people not meeting the eligibility criteria but, for instance, requesting PrEP may be at risk of HIV seroconversion [30,31,32].…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, it is important to highlight that there was a substantial number, varying according to the guideline used, of HIV seroconversions among ineligible participants. It was previously shown that the US CDC criteria failed to identify a considerable proportion of individuals at risk for HIV [9,16,17], and the same was observed in this study and for the other guidelines. Previous research also suggests that people not meeting the eligibility criteria but, for instance, requesting PrEP may be at risk of HIV seroconversion [30,31,32].…”
Section: Discussionsupporting
confidence: 85%
“…Stigma reinforced by the association of PrEP with risky behaviour contributed to the decision of several of the participants to stop PrEP. Unfortunately, for many populations, HIV risk is driven not by behaviour but by one’s sexual network and/or one’s partners’ sexual network [42,43]. For this reason and others, the CDC guidelines predict HIV risk poorly among key populations such as black MSM and heterosexual women [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, for many populations, HIV risk is driven not by behaviour but by one’s sexual network and/or one’s partners’ sexual network [42,43]. For this reason and others, the CDC guidelines predict HIV risk poorly among key populations such as black MSM and heterosexual women [42,43]. In addition to removing barriers to PrEP delivery, PrEP should be normalized as a routine preventive health procedure for people potentially exposed to HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is a growing need for gender-speci c interventions targeting women at risk for HIV, including women with OUD. There is also concern that current PrEP prescribing guidelines may inadvertently disqualify women at risk for HIV (37).…”
Section: Discussionmentioning
confidence: 99%